Elementary school teachers’ support for children with a parent who has cancer in Japan - Yuko Akagawa; Taichi Hatta; Kaori Osawa; Mai Narita; Kingo Endo; Hideaki Andoh; Sachiko Makabe (Journal of Health Sciences)
Introduction: When a parent is diagnosed with cancer, the psychological and social impact on their children can be profound. Teachers play a key role in supporting these children, yet limited research has examined school-based support in Japan. This study aimed to examine the awareness, perceptions, and support practices of elementary school teachers toward children with a parent who has cancer.